Uterine arteriovenous malformation: a rare cause of abnormal uterine bleeding - Sina, Mohim I.; Shakil, Shariful I.; Rahman, M. M.; Khan, Mubarak H.; Rahman, M. M.; Hoque, M. E. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Uterine arteriovenous malformation (AVM) is a rare gynecological entity that usually presents with vaginal bleeding of variable spectrum. High level of suspicion aided by color Doppler ultrasound is needed to confirm the diagnosis. This case report describes a 52-year-old woman G7P6A1 who presented with irregular pervaginal bleeding for 5 years. Her symptom was recurrent, on and off and refractory to hormone therapy. She was diagnosed with uterine AVM on pelvic color Doppler ultrasound that revealed a dilated and hypervascular cystic mass of 6.2×4.1 cm located at right uterine wall where blood flow was bidirectional. As a definitive treatment, open abdominal hysterectomy was performed successfully. This report reminds gynecologists to consider uterine AVM as a rare differential diagnosis of abnormal uterine bleeding (AUB).